Identifying Behavioral Phenotypes and Heterogeneity in Heart Valve Surface Endothelium - Blancas, Alicia A. (Cells Tissues Organs, 2016)
Heart valve endothelial cells (VECs) are distinct from vascular endothelial cells (ECs), but have an uncertain context within the spectrum of known endothelial phenotypes, including lymphatic endothelial cells (LECs). Profiling the phenotypes of the heart valve surface VECs would facilitate identification of a proper seeding population for tissue engineered valves, as well as elucidate mechanisms of valvular disease. Porcine VECs and porcine aortic ECs (AECs) were isolated from pig hearts and characterized to assess known EC and LEC markers. A transwell migration assay determined their propensity to migrate toward VEGF, an angiogenic stimulus, over 24 hours. Compared to AECs, Flt-1 was expressed on almost double the percentage of VECs, 74% vs. 38%. Expression of angiogenic EC markers CXCR4 and DLL4 was >90% on AECs whereas VECs showed only 35% CXCR4+ and 47% DLL4+. AECs demonstrated greater migration (71.5±11.0 cells/image field) than did the VECs with 30.0±15.3 cells/image field (p=0.032). 30% of VECs were positive for LYVE1+/Prox1+, while these markers were absent in AECs. In conclusion, the population of cells on the surface of heart valves is heterogeneous, consisting largely of non-angiogenic VECs and a subset of LECs. Previous studies have indicated the presence of LECs within the interior of the valves, however this is the first study to demonstrate their presence on the surface. Identification of this unique endothelial mixture is a step forward in the development of engineered valve replacements as a uniform EC seeding population may not be the best option to maximize transplant success.